Prevalence of Antimicrobial Resistance in Escherichia coli isolated from Dairy Supply Chain by Phenotypic Methods - Kumar, Amarjeet; Vishweswaraiah, Raghu Hirikyathanahalli; Mallappa, Rashmi Hogarehalli; Bharath, Gunaseka; Kumar, Brijesh; Jaswal, Avinash; Kumar, Naresh (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
A total of 139 E. coli positive isolates from 122 raw milk (57.2%), 10 pasteurized milk (33.3%), and 7 human handlers (35%) were identified by phenotypic methods and 22 of the isolates were further confirmed by PCR. All 22 E. coli (100%) isolates were found resistant to penicillin, oxacillin, erythromycin, and clindamycin. Amongst E. coli isolates, antibiotics resistance was detected towards cefotaxime and amoxyclave (18.7% each) followed by ampicillin (7.98%), trimethoprim (15.82%), tetracycline (10.79%), nalidixic acid (7.91%), and piperacillin (7.79%). Out of 139 isolates, 7.91% isolates were found to be MDR (multidrug resistant) and 4 isolates were confirmed as extended spectrum β-lactamase (ESBL) producers.